Pengaruh Growth Opportunity, Peringkat Proper, Media Exposure dan Tipe Industri terhadap Pengungkapan Emisi Karbon pada Perusahaan LQ45 - saraswati, ayu; Yuniarta, Gede Adi (Universitas Pendidikan Ganesha, 2023)
The phenomenon of climate change is the result of an increase in the amount of carbon emissions. The impact of this phenomenon is an increase in natural disasters that can affect various sectors, including the economic sector. However, the carbon emissions disclosure in Indonesia is still voluntary. The purpose of this research is to determine the effect of growth opportunity, PROPER rating, media exposure, and type of industry on carbon emissions disclosure. The research method used is a quantitative method, the type of data used is secondary data. Carbon emissions disclosure is measured by adopting the CDP (Carbon Disclosure Project) check list. The population consists of companies in the LQ45 Index for the period August 2018-February 2021 and the sample selection using purposive sampling and selected 39 companies from various sectors. The data analysis technique used multiple regression test. The results of this study showed that growth opportunity, PROPER rating, and type of industry have no effect on carbon emissions disclosure, while the media exposure has a positive effect on carbon emissions disclosure.